2019
DOI: 10.1071/cp19014
|View full text |Cite
|
Sign up to set email alerts
|

Field benchmarking of the critical external phosphorus requirements of pasture legumes for southern Australia

Abstract: In recent decades several pasture legumes have been available in southern Australia as potential alternatives to the most widely used annual pasture legume Trifolium subterraneum. Little is known about their soil phosphorus (P) requirements, but controlled environment experiments indicate that at least some may differ in their P fertiliser requirements. In this study, pasture legume varieties, including T. subterraneum as the reference species, were grown at up to four sites in any one year over a 3-year perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 59 publications
3
43
0
Order By: Relevance
“…2), the determined 95% critical value of 15 mg P/kg was the same value previously determined for dryland and irrigated Victorian pastures (Montgomery and Rubenis 1978;Gourley and James 1997) and also consistent with a previously proposed critical value of 20 mg P/kg for 7.5 cm sampling depth for subterranean clover pasture in NSW (Spencer et al 1969). More recent experiments have also found that there was no pasture production response to soil Olsen P values above currently recommended optimum concentrations of 13-16 mg/kg (Cotching and Burkitt 2011;Aarons et al 2015a;Simpson et al 2015;Sandral et al 2019).…”
Section: Phosphorussupporting
confidence: 85%
See 2 more Smart Citations
“…2), the determined 95% critical value of 15 mg P/kg was the same value previously determined for dryland and irrigated Victorian pastures (Montgomery and Rubenis 1978;Gourley and James 1997) and also consistent with a previously proposed critical value of 20 mg P/kg for 7.5 cm sampling depth for subterranean clover pasture in NSW (Spencer et al 1969). More recent experiments have also found that there was no pasture production response to soil Olsen P values above currently recommended optimum concentrations of 13-16 mg/kg (Cotching and Burkitt 2011;Aarons et al 2015a;Simpson et al 2015;Sandral et al 2019).…”
Section: Phosphorussupporting
confidence: 85%
“…Many shorter-term and smaller-scale field studies also support the derived soil test critical values, notably addressing P and K (e.g. Cotching and Burkitt 2011;Aarons et al 2015a;Simpson et al 2015;Sandral et al 2019). Moreover, higher soil test P concentrations are associated with greater and unnecessary rates of P accumulation in the soil (Simpson et al 2014(Simpson et al , 2015 and incur larger risks of P loss to waterways (Melland et al 2008;Gourley and Weaver 2012).…”
Section: Application Of Soil Test Benchmarksmentioning
confidence: 81%
See 1 more Smart Citation
“…Rankings of critical external P requirements were consistent with Hill et al (2005), where P. aquatica, M. stipoides and T. subterraneum were in a group with high external P requirements and Rytidosperma richardsonii (Cashmore) Connor & Edgar in a low group. A similar study by Sandral et al (2019) also found that rankings in the field matched those of controlled conditions. There is no evidence to date that our field studies produced a different or more valid ranking.…”
Section: Discussionmentioning
confidence: 56%
“…Soil fertility has long been an important limitation for pasture production in Australia, and Gourley et al (2019) presents new information on pasture yield responses to addition of phosphorus, potassium and sulfur for regions around Australia. There is also an increasing emphasis on the development of more phosphorus efficient pastures which is highlighted by Sandral et al (2019) and McCaskill et al (2019), while the phosphorus requirements of native pastures in south-eastern Australia was reviewed by Mitchell et al (2019). Nitrogen fertiliser application has become increasingly important in the Australia dairy industry and the balance between production and potential for nitrogen losses was examined by Rawnsley et al (2019).…”
mentioning
confidence: 99%